Attack on Titan. 15 - Isayama, Hajime, 1986- (Kodansha Comics, 2015)
"Hange's interrogation of a Military Police squad has revealed that Krista (a.k.a. Historia Reiss) is the true heir to the throne. The Corps quickly moves to enthrone her as queen, but a homicidal MP leads a squad that abducts Eren and Krista and throws the Corps into disarray. With Erwin arrested and the Survey Corps on the edge of dissolution, are Levi and Hange finally out of options?"--P. [4] of cover.